Perancangan Aplikasi Sistem Informasi Akuntansi Persediaan Barang Pada Toko Minigrosir Jaya Setiawan Sukabumi - Nadya Fajriatul Adni; Destian Arshad Darulmalshah Tamara; Banter Laksana (Indonesian Journal of Economics and Management, 2021)
Toko Minigrosir Jaya Setiawan is a business entity which still uses manual inventory recording system, causing the presentation of inventory information at the store to be slow and inaccurate. This research aims to create an inventory accounting information system application for the store. This research starting from research studies, problem formulation, determination of research objectives, collecting, processing and analyzing data, which aims to find out various obstacles and needs at the store. The next step is to design the system based on the information obtained from the previous step, implementation of the system that has been made, and making research conclusions and also suggestions for the store. The application is designed that it is easy to use and understand the user in recording to presenting inventory information. This application will make it easier for the part of Toko Minigrosir Jaya Setiawan Sukabumi to present inventory information quickly and accurately.